Survey study for diseases of house chickens in villages of Kirkuk governorate - N. A. Jasim (Tikrit Journal of Pure Science, 2023)
This research included (436) infected case of house chickens were diagnosed in villages of Kirkuk in the period (January 2015 to December 2015).The study showed that Newcastle Disease still the most important diseases in poultry of Iraq, with a high percentage of (35.3%) from total cases. The incidence of other diseases were as follow: Parasitic infestations manifested in chickens as Ectoparasites (15%), Fowl pox (14.4%), Internal parasites (13.3%), Bumble foot (7.3%), Fowl Typhoid and Pullorum Disease (6.9%), Necrotic enteritis (4.8%), the low incidence with Fowl cholera (3%) was recorded .